In Vitro Comparison of the Bioactivities of Japanese and Bohemian Knotweed Ethanol Extracts - Pogačnik, Lea; Bergant, Tina; Skrt, Mihaela; Ulrih, Nataša Poklar; Viktorová, Jitka; Ruml, Tomáš (Foods (Basel, Switzerland), 2020)
Knotweed is a flowering plant that is native to temperate and subtropical regions in the northern hemisphere. We evaluated Japanese (Reynoutria japonica Houtt.) and Bohemian (Fallopia x bohemica) knotweed rhizome and flower ethanol extracts and compared them in terms of their biological activities. The specific polyphenols were identified and quantified using HPLC/DAD, and the antioxidant activity was determined using 2,2-diphenly-1-picrylhydrazyl (DPPH) and cellular antioxidant capacity assays. The anticancer activity was evaluated as the difference between the cytotoxicity to cancer cells compared with control cells. The antimicrobial activity was determined using bacteria and yeast. The antidiabetic activity was tested as the ability of the extracts to inhibit α-amylase. Both rhizome extracts were sources of polyphenols, particularly polydatin and (-)-epicatechin; however, the cellular assay showed the highest antioxidant capacity in the flower extract of F. bohemica. The PaTu cell line was the least sensitive toward all knotweed extracts. The flower extracts of both species were less toxic than the rhizomes. However, the activity of the tested extracts was not specific for cancer cells, indicating a rather toxic mode of action. Furthermore, all used extracts decreased the α-amylase activity, and the rhizome extracts were more effective than the flower extracts. None of the extracts inhibited bacterial growth; however, they inhibited yeast growth. The results confirmed that rhizomes of Reynoutria japonica Houtt. could become a new source of bioactive compounds, which could be used for the co-treatment of diabetes and as antifungal agents.
Keywords: herbal medicine; anticancer activity; antimicrobial activity; cellular antioxidant activity; antidiabetic activity; antioxidant activity; polyphenols